Touristic destination and destination image: case study of Slovakia - Bukaiová, Ivana (2018)
The master's thesis aims are to deeply analyze factors of the destination image which contribute to the formation of the secondary and subsequently to the shaping of the primary image. After the analysis of the factor of the secondary image, the same factors are analyzed with same methods also in the primary image part of this project. In the end, this two analyzes are compared, and the results are presented. The results of this work point out that after the real visit of Slovakia, tourists tend to have much more positive image than before. This means that their secondary image, which is formed before the visited it positively affected by the real visit to Slovakia and the primary One of the tools to increase the competitiveness of the country and to support its development is tourism, which, as a sector, occupies an increasingly important place in the national economy because the interest in traveling is constantly increasing. Moreover, to have a positive and steadily growing tourism sector, it is important to have a good marketing strategy with a strong country brand and excellent destination image.